Experimental methods in hydraulic research - Rowiński, Paweł M.; SpringerLink (Online service). (Berlin Springer, 2011)
It is clear that hydraulic research is developing beyond traditional civil engineering to satisfy increasing demands in natural hazards assessment and also environmental research. Our ability to describe processes in nature rests on the observation and experimental methods as well as on theoretical basics of various disciplines. Under such conditions experimental methods draw from various areas of human activities and research, i.e. from physics, biology, chemistry, aerospace research, oceanic research etc. The current volume, is the result of a meeting that took place during the 30th International School of Hydraulics in Poland and  presents both the state of the art and ongoing research projects in which experimental methods play a key role. Authors from numerous leading laboratories and from various countries guarantee a representative sample of different studies at the frontier of the field.
Experimental Investigations of Sandy Riverbed Morphology -- Entrainment Threshold of Loose Boundary Streams -- Particle Imaging Velocimetry and its Applications in Hydraulics -- Turbulent Flow Hydrodynamics and Sediment Transport -- Studies for Nuclear and Pumped-Storage Powerplant Zarnowiec -- Integrated Experimental and Computational Hydraulic Science in a Unique Natural Laboratory -- Estimation of River Banks Influence on Tochoida Shape at the Meridian -- Experimental Study on Gabion Stepped Spillway -- Some Observations on the Similarity of Tracer Data from a Small River.
Electronic reproduction.
Keywords: Hydraulic engineering -- Methodology; Electronic books